?STUDY OF PHYSICO-CHEMICAL PARAMETERS OF AN ARTIFICIAL LAKE OF SINDH (Biological Sciences - PJSIR, 2000)
To determine the cause of elimination of aquatic macrophytes, in aman made lake located in abig Safari Park of Karachi is situated at 24°-50'N latitude and 66°-55'E longitude, sixteen physico-chemical parameters of water were analyzed throughout the water column upto a period of one year from June, 1994 to July, 1995. Analysis of the data shows that most of the chemical constituents were present in high ranges, indicating pollution. The lake is in poor ecological condition as its basin is full of debris which may influence the growth of plants. Special measures to clean the basin will naturally be helpful in making it more picturesque as well as for the exploitation of fish and water fowl hunting.